An Ultrathin, Nanogradient, and Substrate‐Independent WOx‐Based Film as a High Performance Flexible Solar Absorber. Issue 10 (10th July 2019) - Wang, Wei; Wen, Huaixing; Shi, Jing; Su, Jinbu; Li, Zhengtong; Wang, Chengbing; Yan, Xingbin
Abstract : Advances in flexible and wearable energy‐related devices increase the need for highly efficient, low‐cost, ultrathin solar selective absorber coatings (SSACs). Herein, the fabrication of nanogradient WO x ‐based SSACs with excellent properties, including a superior solar absorptance of 0.93, an outstanding thermal robustness of up to 300 °C, and substrate independence, is reported. More importantly, the thickness of WO x ‐based SSACs is only approximately 100 nm, which is substantially thinner than all other reported SSACs. These features arise from the two intrinsically absorptive WO x layers on a thin nanoplasmonic W layer. The deposition process is based on self‐doped reactive sputtering via limited tungsten oxidation due to a small amount of oxygen. The WO x ‐based SSACs on a flexible polyimide sheet demonstrate stable performance, strong adhesion, and bendable nature. The proposed self‐doped fabrication process provides a new way to design cost‐effective ultrathin SSACs to meet the demand for large‐scale flexible energy harvesting and supply applications. Abstract : An ultrathin, nanogradient, and robust WO x ‐based flexible solar absorber is developed by combining the self‐doping concept and intrinsically absorptive WO x film. The total thickness is around 100 nm, which is substantially thinner than all other reported absorbers, but it still possesses super absorptivity, adhesion and bendable nature, and outstanding thermal stability, which is promising for flexible and wearable energy applications.